2021
DOI: 10.1108/ijcma-04-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Articulated dissent and immediacy: a cross-national analysis of the effects of COVID-19 lockdowns

Abstract: Purpose In the midst of the COVID-19 pandemic, this study aims to explore how working remotely might impact the superior–subordinate relationship. Specifically, this study examines how immediacy explains articulated dissent, considers how an individual’s attitudes toward online communication predicts immediacy and articulated dissent and compares these relationships in England, Australia and the USA. Design/methodology/approach Three nations were examined: Australia, England and the USA (n = 1,776). Surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…As dissent can be viewed as an act of conflict (Croucher et al, 2020(Croucher et al, , 2022, it is possible individuals on the receiving side of a dissent message may perceive such messages as bullying. In particular, in organizational cultures that might not promote open communication, or in organizations in which bullying has been prevalent, disagreement/dissent might be perceived differently.…”
Section: Intragroup Conflict Dissent and Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…As dissent can be viewed as an act of conflict (Croucher et al, 2020(Croucher et al, , 2022, it is possible individuals on the receiving side of a dissent message may perceive such messages as bullying. In particular, in organizational cultures that might not promote open communication, or in organizations in which bullying has been prevalent, disagreement/dissent might be perceived differently.…”
Section: Intragroup Conflict Dissent and Bullyingmentioning
confidence: 99%
“…Organizational dissent is defined as the expression of disagreement or contradictory opinions concerning organizational policies and practices (Kassing, 1998). While researchers have demonstrated the benefits of dissenting, research has also shown the act of dissent can be perceived by its audience as a form of conflict (Croucher et al, 2020(Croucher et al, , 2022Zeng, 2018). Researchers have found individuals who dissent are likely to experience bullying for their dissent, often as a form of retaliation (Osborne, 2009;Petrina et al, 2015).…”
mentioning
confidence: 99%
“…Organizations in each nation responded differently, ranging from policy and practice changes, to no specific protections or arrangements, to furloughs and mass redundancies. Such varied responses influence the supervisor-subordinate relationship and overall organizational communication (Croucher et al, 2021a). Thus, we propose the following research questions to explore the extent to which organizational identification and supervisors’ use of immediacy differs nationally:…”
Section: Organizational Identificationmentioning
confidence: 99%
“…Relatedly, this study did not ascertain the potential effect(s) of the presence of COVID-19 on participants. It is possible the presence of a contagion may lead participants to answer questions differently on surveys (Croucher et al, 2021a(Croucher et al, , 2021b(Croucher et al, , 2021d. Research should continue to explore this potential effect.…”
Section: Practical Implications Limitations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation